Developing a finite difference time domain (fdtd) software for solving large electromagnetic problems - Islam, Md. Rafiqul (s.n, 2012)
This research aims to develop a novel domain decomposition finite-difference time domain technique (FDTD) for solving large electromagnetic radiation and scattering problems. Modifications have been made to the conventional FDTD technique so that serial subdomains can be simulated. The computational domain is divided into manageable, moderate-size subdomains with overlapping regions. To terminate the subdomains so that they can absorb outgoing waves, Perfectly Matched Layers (PML) are used. The tangential electric fields at the boundaries are equal. Therefore, the field stored in preceding subdomain serves as an equal and initial excitation field for the succeeding subdomain. This leads to the serial application of subdomains instead of large single electromagnetic structure so that the simulation burden to computer memory and the available computational resource is obviated. This method has the ability to simulate accurately large electromagnetic problems which are difficult to handle using the direct application of the FDTD method. The simulation results tangential electric fields of subdomains compare well with the direct FDTD solution of single large electromagnetic structure. Application of the DDFDTD method also shows remarkable improvement over simulation time.